Effect of Miswak (Salvadora persica) Toothbrushing on Salivary Flow Rate in Children with Down Syndrome: a Pre–Post Controlled Study - Artika, Suci Idia; Satrio, Rinawati; Ramadhani, Amilia (Jurusan Kedokteran Gigi Fakultas Kedoketaran Universitas Jenderal Soedirman, 2026)
Background: Saliva plays a vital role in maintaining oral health. Children with Down syndrome often experience reduced salivary flow due to salivary gland hypoplasia, increasing their risk of oral health problems. Miswak (Salvadora persica), a traditional toothbrush, provides both mechanical and chemical stimulation that may enhance salivary secretion. This study aimed to evaluate the effect of miswak toothbrushing on salivary flow rate in children with Down syndrome. Methods: A controlled pre-post study was conducted among 20 children with Down syndrome in SLB C-C1 Yakut Purwokerto and SLB ABCD Banyumas, Central Java, Indonesia. Participants were randomly assigned to a miswak group or a conventional toothbrush group. Saliva was collected using the spitting method before and after brushing. Results: The miswak group showed a significant increase in salivary flow rate (0.21 to 1.01 mL/min), compared to a modest increase in the control group (0.21 to 0.31 mL/min). The difference between groups was statistically significant (p < 0.01). Conclusions: These findings suggest that miswak toothbrushing may be an effective method to enhance salivary flow in children with Down syndrome, potentially contributing to improved oral health outcomes. Keywords: Down syndrome, salivary flow rate, Salvadora persica, oral health